Teacher Problems in Learning to Write Exposition Text in Elementary School - Sukmana, Vegyta Tresya Putri; Rahman (International Conference on Elementary Education, 2022)
. Language learning has four skills, one of which is writing skills. Writing skills are closely related to critical thinking because by writing students can develop their thinking about something through writing. The purpose of this study was to explore the activities of teaching writing exposition texts at the elementary school level in terms of models, willingness to study hours, learning resources used and the obstacles faced by teachers in several elementary schools in teaching writing exposition texts. The research method used is a survey method with a cross-sectional survey design. The respondents involved in this study were 20 elementary school teachers who teach in the high class and came from 12 different elementary schools. The survey results show that in the teaching process of writing exposition texts, the majority of teachers still use conventional learning models with the lecture method and make students passive and by utilizing available learning resources in schools so that it has an impact on indicators of learning to write exposition texts, namely about writing essays, compiling and paragraph development, as well as students' effective sentence writing is low.